Analysis of sukuk cross-default clause: a fiqh perspective - Zakariyah, Habeebullah; saheed, Abdullahi Busari (IIUM Press, International Islamic University Malaysia, 2019)
In recent time, there have been incessant Sukuk default cases which are posing a severe challenge to the growth of the nascent Islamic finance Industry. Institutions and principal officers in the industry are often concern about appropriate mechanisms that can protect the right and interest of the Sukuk-holders without violating Shari’ah-compliant risk. It is significant to note that there is a difference between Sukuk default and default event. Sukuk defaults happen when the obligor fails in fulfilling their financial obligations as indicated in the contractual agreement. Default event is various circumstances that can trigger Sukuk default. Default event can be in the form of credit risk and moral risk. Cross-default is an example of a default event that has attracted the attention of legal and Shari’ah scholars. Scholars and experts are considering the juristic status of cross-default mechanism that can be used to protect the right and interest of creditors by juxtaposing it with the principles of justice and equity in Islamic law. This paper aims to explore the legality and fairness of cross-default in Islamic jurisprudence. This study explains the concept of cross-default, how it works, review of what constitutes legality and morality of cross-default in Islamic legal theory. The study also employs the juristic analysis method to examine the opinions of contemporary scholars and expert of Islamic finance on the fairness of Sukuk crossdefault.